Business Strategies and Competitive Advantage: Evidence from Flour Mill Companies in Lagos State, Nigeria - A. J., Egwakhe; R. B., Falana; O. O., Asikhia; N., Magaji (Journal of Economics and Behavioral Studies, 2020)
The authors argued from business strategies perspective to understand competitive advantage among homogenous producers. The population consisted of top and functional managers of flour mill companies in Lagos State, Nigeria. Cross sectional survey research design was adopted and primary data were collated and used. The research instrument was an adapted questionnaire. Its validity and reliability were statistically determined. Six hundred and twenty copies of the questionnaire were administered and 605 retrieved. Econometric equation was formulated and multiple regression analysis was employed for data analysis. Business strategies were found to have significantly affected competitive advantage. The study recommended product differentiation and portfolio diversification in order to achieve competitive advantage.